Kväveomsättning i gräsmark med olika artantal och artsammansättningar - Sanfridsson, Anna-Carin (SLU/Dept. of Agricultural Research for Northern Sweden, 2005)
This study was carried out at the Swedish University of Agricultural Sciences, Dept. of Agricultural Research for Northern Sweden. The aim of the study was to determine how plant species richness and diversity influence the nitrogen pools and nitrogen fluxes in the soil. Plant and soil samples from a biodiversity experiment in grasslands were used. Thirty plots with 12 grassland plant species (legumes, grasses, and non-legume herbs), combined from 1-12 species were investigated. The aboveground biomass was harvested in mid-August 2002. In late October the soil was sampled and collected for analyses in the laboratory. Plant diversity and composition play an important role for nitrogen cycling in soil and sustainability of plant production. The total plant biomass increased with increased number of species and when legumes were included in the plant communities. Nitrogen concentration and nitrogen content in plant biomass increased with an increasing fraction of legumes. Anaerobic nitrogen mineralization rate was slower in soil from plots with monocultures than from more species-rich plant communities, especially 12-species mixtures. Potential nitrification was positively correlated to legume biomass as a percentage of total plant biomass. Communities with a mix of legumes, grasses and herbs had the highest concentrations of ammonium (extracted from soil by KCl). This could be explained by high nitrogen mineralization. Concentrations of nitrate were much higher in plots with only legume species. The results from this study support the view that high plant diversity can reduce the risk for nitrate leaching and also allow a more efficient exploitation of available resources. Detta projekt utfördes vid Sveriges lantbruksuniversitet, Institutionen för norrländsk jordbruksvetenskap, Umeå. Syftet med studien var att undersöka hur antalet växtarter och artsammansättningen påverkar kväveomsättningen i marken. Studien omfattar 30 försöksytor med 12 olika arter av gräsmarksväxter (gräs, baljväxter och örter) i ...